Accurate Retrieval of Target Structures and Laser Parameters of Few-Cycle Pulses from Photoelectron Momentum Spectra - Micheau, S.; Chen, Zhangjin; Le, A. T.; Rauschenberger, J.; Kling, M. F.; Lin, C. D. (My University, 2009)
We illustrate a new method of analyzing three-dimensional momentum images of high-energy photoelectrons generated by intense phase-stabilized few-cycle laser pulses. Using photoelectron momentum spectra that were obtained by velocity-map imaging of above-threshold ionization of xenon and argon targets, we show that the absolute carrier-envelope phase, the laser peak intensity, and pulse duration can be accurately determined simultaneously (with an error of a few percent). We also show that the target structure, in the form of electron-target ion elastic differential cross sections, can be retrieved over a range of energies. The latter offers the promise of using laser-generated electron spectra for probing dynamic changes in molecular targets with subfemtosecond resolution.